Challenges of OPEC and its Implications to Qatar Economic Policies - R. Pazhanisamy; Bharathi Muruganandam (ZBW - Leibniz Information Centre for Economics, 2024)
The Organization of Petroleum Exporting Countries (OPEC) has been one of the most influential organizations in the global energy sector which controls a significant portion of the world's oil reserves and has often influenced global oil prices through international trade policies such as quotas and strategic decision-making. The rapid global shift towards renewable energy, increased awareness of climate change, and technological advancements in energy production pose various challenges to OPEC's relevance and future. As a member of OPEC, Qatar's economic strategies and policies are intricately linked to the future of OPEC's economy. In this context this paper attempted to explore the future of the OPEC economy with the perspective of energy transitions and how this could shape Qatar's economic policies so that its economy can mov forward. The central premise of this paper is that while OPEC's influence on global oil markets may diminish due to energy transitions and global environmental initiatives, member countries such as Qatar will need to adopt innovative economic policies that ensure sustained prosperity even in a low-oil-demand scenario. With energy diversification gaining momentum globally, this paper outline what kind of policy decisions today will significantly impact the economic and political stability of OPEC for sustainability.
Keywords: E6; F4; H3; L51; M1; 330; Zero carbon solution to Qatar; Challenges of OPEC; Economic Policy for Qatar; Sustainable oil trade; Global Energy transitions; OPEC alternative Economic Policies